Wayang Orang dan Celemek Bergambar untuk Melatih Kemandirian dan Adab Makan - Suyadi, Suyadi; Wulantaka, Rr. Nazauma Nareswara (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Teachers and parents have the task and responsibility to educate children to have good character. One of the characters that need to be trained in early childhood is independence and food courtesy. The method used by the author to practice this is storytelling with APE puppets and pictorial aprons. The research method used is qualitative. The results and discussion of this study found that B3 group students were able to answer questions correctly. This shows that APE puppet people used as media for storytelling for writers are effective for training independence of early childhood. With this APE illustrated apron group B3 students can better understand what is good eating habits and eating habits that should not be done.